Tren penelitian sosiologi pendidikan menggunakan analisis bibliometrik - Arbi Arbi; Abu Anwar; Eva Dewi; Syarifuddin Syarifuddin; Alfiah Alfiah; Suhaimi Suhaimi; Arwan Arwan; Miftahuddin Miftahuddin; Herlina Herlina; Istiqomah Istiqomah; M. Fahli Zatrahadi; Ifdil Ifdil (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Research on the sociology of education was carried out because it was driven by the need to understand how education influences and is influenced by social factors, and how to improve the education system so that it can provide fair and equitable opportunities for all individuals. The purpose of the research is to find out various studies on sociology education and future trends on this theme. The research method uses bibliometric analysis with the help of software including openrefine, vosviewer, and Rstudio. The database is obtained through Scopus because it is more trusted and has a worldwide reputation. Data is taken in csv form which is then processed with the help of the software. The results showed that research into sociology education had existed since 1924. The highest-ranking author in publications on this theme was Jaworski Ja, followed by Roucekjs then Linggard B and Zhang L. Several future research topics related to sociology education. Some of them contain qualitative studies, the internet, sociology, human experiments, emotional experiences, emotional expressions, product design, decision making, social interactions, health care quality, medical sociology, and health behavior.